The Indonesian State's Transitional Efforts in Developing Renewable Energy - Fadya Dwi Kundaryanti; Pratiwi Ayu Retno Sari; Wahyu Kurniawati (Educare: Journal Educational and Multimedia, 2024)
In a country, energy plays an important role in everyday life. Energy is defined as the ability to do work. All objects that can produce energy are called energy sources. Energy sources themselves are divided into two, namely non-renewable energy and renewable energy. Renewable energy is a source obtained from the earth's natural resources which are unlimited or will not run out such as wind, sun and others. The use of renewable energy sources has both positive and negative impacts on the surrounding environment. It is not surprising that renewable energy sources have many positive impacts, including reducing pollution by using environmentally friendly fuel or reducing greenhouse gas emissions, maintaining public health.